Electropolymerization of Thiophene‐Based Monomers with Different Spatial Structures: The Impact of Monomer Structure on Electrochromic Properties. Issue 2 (2nd December 2021) - Zhang, Yuhang; Li, Rui; Chang, Lijing; Ma, Yang; Hou, Yanjun; Niu, Haijun
Abstract: The development prospect of conductive electrochromic (EC) polymers requires the design of polymers with high performance and good stability. Here, a new scheme is designed to enhance EC properties by adjusting the monomer molecular structure. Four monomers with different structures based on thiophene and 3, 4‐ethylenedioxythiophene (EDOT) are designed and synthesized. The corresponding polymer films (P1, P2, P3, and P4) are prepared by electrochemical polymerization at low applied potential. The spatial structure–performance relationship of precursors with different structures and polymers is systematically discussed. In the electropolymerization experiments, it is noted that P3 has no EC property. This may be connected to the spatial structure of P3 polymerization which is not suitable for charge transporting. By contrast, the other three polymers exhibit excellent electrochemical properties. The diffusion rate higher of P1 has also been corroborated by using electrochemical impedance spectroscopy (EIS) spectrum. The P1 film has the best stability and fastest colorized time among the samples; such superior electrochemical property may be associated with the closely stacked formed by the unique sheet‐like spatial structure. The design of the space structure has a significant impact on the optical and electrical properties of the polymer film. Abstract : In this study, four polymer films are prepared with different spatial structures through electropolymerization, and the relationship between structure and electrochromic (EC) properties is carefully analyzed. Due to different polymer structures, the electrochemical properties of the four polymers all show distinct changes. Various tests indicate that the star‐shaped structure of P1 can be used to design highly efficient electrochromic materials.